2011
DOI: 10.1289/ehp.1002060
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties Associated with Quantifying Climate Change Impacts on Human Health: A Case Study for Diarrhea

Abstract: BackgroundClimate change is expected to have large impacts on health at low latitudes where droughts and malnutrition, diarrhea, and malaria are projected to increase.ObjectivesThe main objective of this study was to indicate a method to assess a range of plausible health impacts of climate change while handling uncertainties in a unambiguous manner. We illustrate this method by quantifying the impacts of projected regional warming on diarrhea in this century.MethodsWe combined a range of linear regression coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 35 publications
3
119
0
Order By: Relevance
“…Although uncertainties exist, our study has provided evidence to support a positive association between temperature and numbers of cases of bacillary dysentery in a Chinese setting, which is consistent with the increasing diarrheal diseases associated with rising temperatures. 43 In conclusion, our study indicates that bacillary dysentery is mainly related to the temperatures in the study region in China. Increasing temperature may bring more diarrheal disease burden in the tropical and subtropical areas in China.…”
Section: Discussionmentioning
confidence: 56%
“…Although uncertainties exist, our study has provided evidence to support a positive association between temperature and numbers of cases of bacillary dysentery in a Chinese setting, which is consistent with the increasing diarrheal diseases associated with rising temperatures. 43 In conclusion, our study indicates that bacillary dysentery is mainly related to the temperatures in the study region in China. Increasing temperature may bring more diarrheal disease burden in the tropical and subtropical areas in China.…”
Section: Discussionmentioning
confidence: 56%
“…[1][2][3] Epstein [4] reviewed several examples of how climate change and variability (and extreme weather events) have been associated with the emergence and re-emergence of infectious diseases, either directly (as a result of the biology of vector-borne diseases) or indirectly by, for example, altering the hydrological cycle. Kolstad and Johansson [5] took a generic approach in examining the potential impact of long-term climate projections on diarrhoea in low latitudes and showed that with the most conservative estimates the incidence would increase by 8 -11% in their study areas, concluding that in the face of statistical climate change uncertainty, an urgent need for more empirical research exists. In more detailed examples, the role of varying climate modes (e.g.…”
Section: Understanding Climate In Relation To Health In Generalmentioning
confidence: 99%
“…For China (region WPR-B), flood and malaria related risks were projected to increase, and diarrhea and malnutrition risks are projected to increase and decrease, respectively, but nominally (McMichael et al, 2004). However, future projections of health impacts due to climate change are uncertain (Kolstad and Johansson, 2011;McMichael, 2006;Patz et al, 2005).…”
Section: Mcmichael Et Al (2004) Find Through a Regional Human Healthmentioning
confidence: 99%